Integrating Thai and Chinese cultural symbols in contemporary painting: A cross-cultural artistic creation model - Yuan, Liu Cai; Khiatthong, Thongchue; Addok, Mathasit (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to develop a cross-cultural artistic creation model that integrates Thai and Chinese cultural symbols in contemporary paintings. It addresses the need for a methodological synthesis that bridges traditional art-historical scholarship and design-oriented approaches to preserve cultural heritage while fostering innovative practices. Adopting a qualitative research design, this study employs comparative visual analysis, cultural semiotics, and interpretive methodologies. Traditional Thai and Chinese paintings were analyzed in terms of their symbolic repertoires, aesthetic philosophies, and narrative structures. Semiotic interpretation was applied to decode recurring symbols, such as the lotus, naga, dragon, and phoenix, and to explore their roles as dynamic signifiers in both traditions. The analysis reveals both convergence and divergence between Thai and Chinese symbolic systems. Thai paintings emphasize narrative pedagogy, vibrant polychromy, and Buddhist cosmology, whereas Chinese paintings prioritize contemplative abstraction, monochromatic harmony, and Daoist-Confucian philosophy. The findings demonstrate that cultural symbols function as living mediators linking heritage, ethics, and identity and can be hybridized to form a coherent intercultural visual language. This study proposes the Anzhi model, a cross-cultural creative framework that positions cultural symbols as semiotic bridges between tradition and innovation. This model contributes theoretically to semiotic and symbolic culture studies and practically to the design of strategies for intercultural artistic creation. The proposed model provides actionable guidelines for artists, designers, and educators to embed cultural meaning into contemporary visual arts, thereby supporting cultural continuity, global dialogue, and sustainable creative practices aligned with SDGs 11 and 16.